2017
DOI: 10.1007/s00702-017-1781-0
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared spectroscopy (NIRS) and vagus somatosensory evoked potentials (VSEP) in the early diagnosis of Alzheimer’s disease: rationale, design, methods, and first baseline data of the Vogel study

Abstract: Functional near-infrared spectroscopy (fNIRS) and vagus somatosensory evoked potentials (VSEP) show deviant patterns in subjects with Alzheimer's disease (AD) compared to healthy controls. We now aimed at testing the predictive value of these methods in the early diagnosis of AD. The Vogel study is a prospective, observational, long-term follow-up study with three time points of investigation within 6 years. Residents of the city of Würzburg born between 1936 and 1941 were recruited. Every participant underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 172 publications
0
14
0
Order By: Relevance
“…We identified 40 studies performed with a total of 977 AD and 477 MCI patients (208 amnestic MCI), as well as with 792 age-matched HC subjects (Table 2) Most studies were addressed to the monitoring of tissue oxygenation [65][66][67][68][69][70], the investigation of functional resting-state activity and connectivity [64,[71][72][73], the assessment of specific cognitive functions [74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93] such as visuospatial deficits [94,95] and additional ecological applications [96,97]. Though most studies reported cross-sectional reports, we also retrieved six longitudinal ones [98][99][100][101][102][103], thus strongly supporting the idea that fNIRS can represent a viable tool for long-term monitoring of cerebral activity from the early phases of the disease or during rehabilitation.…”
Section: Fnirs In Alzheimer's Disease and Mild Cognitive Impairmentmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 40 studies performed with a total of 977 AD and 477 MCI patients (208 amnestic MCI), as well as with 792 age-matched HC subjects (Table 2) Most studies were addressed to the monitoring of tissue oxygenation [65][66][67][68][69][70], the investigation of functional resting-state activity and connectivity [64,[71][72][73], the assessment of specific cognitive functions [74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93] such as visuospatial deficits [94,95] and additional ecological applications [96,97]. Though most studies reported cross-sectional reports, we also retrieved six longitudinal ones [98][99][100][101][102][103], thus strongly supporting the idea that fNIRS can represent a viable tool for long-term monitoring of cerebral activity from the early phases of the disease or during rehabilitation.…”
Section: Fnirs In Alzheimer's Disease and Mild Cognitive Impairmentmentioning
confidence: 99%
“…At a high cognitive load, more evident hemodynamic responses were associated with higher training gains, thus indicating that PFC activity may be considered as predictive of WM training effectiveness. Finally, Polak et al [103] are currently conducting a 10-year study aimed at evaluating, whether vagus somatosensory evoked potentials and fNIRS, together with several other outcome measures (Table 2), could serve as future diagnostic markers of AD and as a monitoring tool of cognitive decline. This study is expected to end in 2021 but several results have already been published, such as the work by Zeller et al [72] and Katzorke et al [84] already mentioned in this review.…”
Section: Longitudinal Monitoringmentioning
confidence: 99%
“…Two groups of patients were recruited in parallel. The first consists of 329 participants who were recruited during the second interview of a long-term cohort study 8 . None of them suffered from a severe internal, neurologic or psychiatric disease within the last year before sampling and this group is therefore referred to as reference group in the following.…”
Section: Recruitment Of Participantsmentioning
confidence: 99%
“…To overcome this issue, further diagnostic tools are needed and are currently under development, including biomarkers to predict and investigate AD or MCI 8,9 . Important criteria for the ideal biomarker are, amongst others, reproducibility, feasibility, cost, sensitivity and specificity 10 .…”
mentioning
confidence: 99%
“…Cortical responses to VNS may be used to screen subjects for neurodegenerative diseases, to assist the diagnosis and to track disease progression (Metzger FG et al . 2012; Polak T et al 2017). Furthermore, EEG markers, like VEPs, could be used to predict effectiveness of VNS therapy (Ravan M et al 2017).…”
Section: Introductionmentioning
confidence: 99%